2022
DOI: 10.1016/j.patcog.2021.108423
|View full text |Cite
|
Sign up to set email alerts
|

Improved time series clustering based on new geometric frameworks

Abstract: Most existing methods for time series clustering rely on distances calculated from the entire raw data using the Euclidean distance or Dynamic Time Warping distance. In this work, we propose to embed the time series onto higher-dimensional spaces to obtain geometric representations of the time series themselves. Particularly, the embedding on R n×p , on the Stiefel manifold, and on the unit sphere are analyzed for their performances with respect to several yet well-known clustering algorithms. The gain brought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…After several attempts, it is found that when the residual sequence is fitted by AR-GARCH model, the AR term in the final fitting result is not significantly 0, so it is considered that there is no autocorrelation in the residual sequence [4] .Therefore, after removing the autoregression term (AR term) of residual, the conditional heteroscedasticity model was fitted again [5] .Through experiments, it is found that among many models (ARCH model, model etc. ), EGARCH(1,1) model has the best fitting effect.…”
Section: Egarch Model Is Used To Fit Residual Sequence and Its Fittin...mentioning
confidence: 99%
“…After several attempts, it is found that when the residual sequence is fitted by AR-GARCH model, the AR term in the final fitting result is not significantly 0, so it is considered that there is no autocorrelation in the residual sequence [4] .Therefore, after removing the autoregression term (AR term) of residual, the conditional heteroscedasticity model was fitted again [5] .Through experiments, it is found that among many models (ARCH model, model etc. ), EGARCH(1,1) model has the best fitting effect.…”
Section: Egarch Model Is Used To Fit Residual Sequence and Its Fittin...mentioning
confidence: 99%
“…The idea behind clustering is to form several groups or clusters of unlabelled elements so that the data points of each cluster are similar to each other. 1 An ordered collection of values for a variable that were taken at predetermined intervals of time is known as a time series. 2 Time series analysis frequently involves forecasting future values in a time-series context as well as the recognition and application of patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering is a widely-known unsupervised machine learning algorithm. The idea behind clustering is to form several groups or clusters of unlabelled elements so that the data points of each cluster are similar to each other 1 . An ordered collection of values for a variable that were taken at predetermined intervals of time is known as a time series 2 .…”
Section: Introductionmentioning
confidence: 99%